Hydrogel composition and laser micropatterning to regulate sciatic nerve regeneration. (8th January 2018) - Berkovitch, Yulia; Cohen, Talia; Peled, Eli; Schmidhammer, Robert; Florian, Hildner; Teuschl, Andreas H.; Wolbank, Susanne; Yelin, Dvir; Redl, Heinz; Seliktar, Dror
Abstract: Treatment of peripheral nerve injuries has evolved over the past several decades to include the use of sophisticated new materials endowed with trophic and topographical cues that are essential for in vivo nerve fibre regeneration. In this research, we explored the use of an advanced design strategy for peripheral nerve repair, using biological and semi‐synthetic hydrogels that enable controlled environmental stimuli to regenerate neurons and glial cells in a rat sciatic nerve resection model. The provisional nerve growth conduits were composed of either natural fibrin or adducts of synthetic polyethylene glycol and fibrinogen or gelatin. A photo‐patterning technique was further applied to these 3D hydrogel biomaterials, in the form of laser‐ablated microchannels, to provide contact guidance for unidirectional growth following sciatic nerve injury. We tested the regeneration capacity of subcritical nerve gap injuries in rats treated with photo‐patterned materials and compared these with injuries treated with unpatterned hydrogels, either stiff or compliant. Among the factors tested were shear modulus, biological composition, and micropatterning of the materials. The microchannel guidance patterns, combined with appropriately matched degradation and stiffness properties of the material, proved most essential for the uniform tissue propagation during the nerve regeneration process.